Avaliação de parâmetros cardiometabólicos e supercrescimento bacteriano de intestino delgado em indivíduos com doença hepática gordurosa não alcoólica: um estudo transversal - Lira, Marília Marques Pereira (2020)
Non-alcoholic fatty liver disease (NAFLD) is characterized by a spectrum of diseases that include fatty liver, steatohepatitis and liver cirrhosis, and has been associated with small intestinal bacterial overgrowth (SIBO) and cardiovascular diseases. In this cross-sectional study, we aimed to evaluate cardiometabolic parameters and the presence of small intestinal bacterial overgrowth in individuals with non-alcoholic fatty liver disease and different degrees of liver fibrosis estimated by the liver disease fibrosis score (NAFLD fibrosis score - NFS). This study involved 78 participants with age ranging between 18 and 75 years, both gender, who were allocated into three different groups. Group 1: Healthy controls (n = 30), individuals with no evidence of liver, heart or metabolic disease; Group 2: 17 individuals with non-alcoholic fatty liver disease and low estimated risk of advanced fibrosis (AF) and Group 3: individuals with non-alcoholic fatty liver disease and high estimated risk of advanced liver fibrosis (n = 31). In all groups, anthropometric measurements (body weight, height and body mass index), blood pressure and heart rate variability (HRV) measures were evaluated. Only individuals diagnosed with non-alcoholic fatty liver disease (Groups 2 and 3) underwent blood biochemical analyzes and breath test of hydrogen exhaled with glucose to small intestinal bacterial overgrowth diagnosis. The average age was (± standard deviation) 41.03 ± 14.72 years. Both groups of individuals with liver disease had a higher age and body mass index when compared to the control group (p <0.01). The low frequency component (LF) and the low / high frequency ratio (LF / HF ratio) were lower in patients with liver disease associated with a high estimated risk of advanced fibrosis than in individuals with non-alcoholic fatty liver disease and low risk of advanced fibrosis (p = 0.04 and p = 0.02, respectively). Hypoalbuminemia and thrombocytopenia were lower in subjects with worse estimated liver fibrosis (p <0.01 and p = 0.02). Prevalence of small intestinal bacterial overgrowth was similar between groups. The present study shows that non-alcoholic fatty liver disease is associated with an autonomic cardiac dysfunction and the higher impairment being noted in individuals with the worst degree of liver fibrosis estimated by score.